2013
DOI: 10.1177/1457496913492463
|View full text |Cite
|
Sign up to set email alerts
|

Declining Cholecystectomy Rate During the Era of Statin Use in Finland: A Population-Based Cohort Study Between 1995 and 2009

Abstract: Background and Aims: Aging with comorbidities, obesity, and rapid recovery from operation may increase the need for laparoscopic cholecystectomy, but long-term use of statins may be associated with a decreased risk of gallstones. This population-based cohort study presents the changing rate and causative factors of laparoscopic cholecystectomy in Finland during the era of statin use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Our findings are in line with the one previous study focusing on one individual type of BTC (cholangiocarcinoma) in Taiwan, which reported that the adjusted OR for statin use versus nonuse for cholangiocarcinoma was 0.80 (95%CI: 0.71-0.90). [27] The results are also consistent with studies that have demonstrated a decreased risk of gallstone disease, [12,13,14,15] a risk factor for BTCs, [28] especially GBC. [1,2] Statins could potentially reduce risk of BTCs through suppression of biliary cholesterol secretion and saturation and anti-inflammatory and endothelial effects.…”
Section: Comparison To Other Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings are in line with the one previous study focusing on one individual type of BTC (cholangiocarcinoma) in Taiwan, which reported that the adjusted OR for statin use versus nonuse for cholangiocarcinoma was 0.80 (95%CI: 0.71-0.90). [27] The results are also consistent with studies that have demonstrated a decreased risk of gallstone disease, [12,13,14,15] a risk factor for BTCs, [28] especially GBC. [1,2] Statins could potentially reduce risk of BTCs through suppression of biliary cholesterol secretion and saturation and anti-inflammatory and endothelial effects.…”
Section: Comparison To Other Studiessupporting
confidence: 87%
“…Statins are commonly used cholesterol-lowering medications that have demonstrated effectiveness in the primary and secondary prevention of cardiovascular disease. [11] Several studies have shown that statins are associated with a lower risk of gallstone disease (gallstones or a history of cholecystectomy) [12,13,14,15], but associations with BTCs have not been well studied. To further our understanding of the associations between statins and BTCs, we thus conducted a nested case-control study within a large database of primary care electronic medical records -the United Kingdom (UK) Clinical Practice Research Datalink (CPRD).…”
Section: Introductionmentioning
confidence: 99%
“…From a population perspective, however, resectional surgery represents a small part of upper abdominal surgery in absolute numbers. Cholecystectomy was the most common procedure in the present study, 173/100 000 inhabitants, and similar operation rates have been reported [15][16][17]. Surgical traditions, and local indications for surgical or conservative treatment of primary cholecystitis, influence the number of cholecystectomies per capita, as well as simultaneous cholecystectomies performed in liver and pancreatic resections.…”
Section: Countiessupporting
confidence: 79%
“…In the analysis of 10 174 LCs by Z’graggen and co-workers [ 9 ], bleeding was also the most frequent intraoperative complication occurring in 1,97 % of the cases. In a Finnish series of 1581 LCs, incidence of all bleeding complications was 1.1 % [ 22 ] and bleeding complications requiring reoperation occurred in 0.5 % of the cases [ 23 ]. Roslyn and co-workers [ 4 ] reported the overall incidence of bleeding complications of 0.4 % in the analysis of 42 474 OCs.…”
Section: Discussionmentioning
confidence: 99%